Service Quality and Customer Satisfaction within Festival and Special Event - Norazirah, Ayob; Abas, Said (2010)
The concept of customer satisfaction and service quality are notably two important concepts in marketing. Indeed, the two concepts are important in addressing theoretical as well as practical issue for marketers and consumer researchers. Numerous researches have been found discussing various issues related to the two constructs in various field areas. Midst all the debates, there is an existing discussion on a conceptualization of relationship between satisfaction and service quality that is argued to be relevant especially to the field of festival and special event and generally to other tourism and recreation fields. The conceptualizations seemed to receive supports from a number of event researchers and thus adapted and further examined in their studies. This paper presents a review on the service quality and satisfaction constructs and their relationship illustrated by Crompton and Love (1995), Childress and Crompton (1997), and Baker and Crompton (2000). Examples of past studies that have supported and further investigated the conceptualization are also included.